2015
DOI: 10.1080/19373260.2015.1014304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PET fiber arrangement and dimensions on mechanical properties of concrete

Abstract: Concrete has low tensile strength and crack resistance. Its weaknesses could be enhanced with the addition of fiber. Polyethylene terephthalate (PET) fibers are generally used in concrete as discrete reinforcement in substitution of steel fiber. Fibers obtained by hand cutting of PET bottles are in the form of straight slit sheets, which impart weaker bonding in concrete matrix. The bonding of the fibers however may be improved by using other geometries such as flattened-end sheet pattern. So far, there are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 15 publications
1
19
0
9
Order By: Relevance
“…The results showed that the percentage of increase of rupture strength and impact resistance was 34.27% and 157.14%, respectively, for reinforced concrete compared with plain panels. The influence of PET fibers geometry on the properties of concrete was investigated, Marthong and Sarma [41,42] showed that fiber geometry has a small effect on the workability of concrete but a significant contribution to the mechanical properties of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the percentage of increase of rupture strength and impact resistance was 34.27% and 157.14%, respectively, for reinforced concrete compared with plain panels. The influence of PET fibers geometry on the properties of concrete was investigated, Marthong and Sarma [41,42] showed that fiber geometry has a small effect on the workability of concrete but a significant contribution to the mechanical properties of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…In one of the research polyethylene, terephthalate fibers were used to determine the concrete mechanical properties; with the main concern to measure the influence of various dimensions and geometries on the concrete mechanical properties. Marthong's conclusions declare that the workability effected by a very small amount by changing the fibers geometry [12].…”
Section: Introductionmentioning
confidence: 97%
“…Use of these waste bottles in any form would be benefitted not only by the prevention of environmental pollutions, but also by energy saving in their disposals. Excellent contribution of PET fibre in enhancing the mechanical properties of concrete has been studied Foti 2011Foti , 2013Fraternali et al 2011;Won et al 2010;Marthong 2015). Most of the authors pointed out that the fibre contents mainly influence the performance of concrete.…”
Section: Introductionmentioning
confidence: 98%
“…At a resin content of 9% strength and durability was nearly unaffected.Partially replacing the NCA by RCA, fly ash added to cement content Drawbacks induced by the use of recycled aggregate in concrete could be minimised with the addition of 25-35% fly ash.Polymer based treatment applied to RCA showed lower absorption and better fragmentation resistance Marthong (2015). PET fibre obtained by hand cutting from consumer PET bottle Slight reduction in the workability of concrete in terms of slump.…”
mentioning
confidence: 99%